Multiple analytical perspectives of mitochondrial genes in the context of preeclampsia: potential diagnostic markers - Li, Can; Liu, Fang; Li, Chao; Zhao, Xiangzhong; Lv, Qiulan; Jiang, Aiping; Zhao, Shuping (Frontiers in Immunology, 2025)
Preeclampsia(PE) is closely linked to adverse maternal and fetal outcomes. Given the pivotal roles of mitochondria in various human diseases and the limited research on their involvement in PE, this study identified biomarkers linked to mitochondrial metabolism in PE and their roles in its pathogenesis. Data from three datasets were integrated using the ComBat algorithm to mitigate batch effects. Differential expression analysis identified genes differentially expressed between PE cases and Control group. Cross-referencing these genes with mitochondrial energy metabolism-related genes (MMRGs) isolated mitochondrial energy metabolism-related differentially expressed genes (MMRDEGs). GO and KEGG analysis were performed to elucidate the functions of the MMRDEGs. A diagnostic model using Random Forest and logistic regression was validated by ROC curve analysis. mRNA expressions of OCRL, TPI1, GAPDH, and LDHA were quantified via qPCR. Immune characteristics were explored, and PPI, mRNA-miRNA, mRNA-TF and mRNA-RBP interaction networks were constructed. AlphaFold analyzed protein structures of OCRL, TPI1, GAPDH, and LDHA. A total of 1073 DEGs and 24 MMRDEGs were identified. OCRL, TPI1, GAPDH, and LDHA formed the diagnostic model, which were predominantly enriched in pyruvate metabolism, glycolysis, and ATP metabolism pathways. CIBERSORT highlighted immune cell composition variations between PE and Control groups. OCRL, TPI1, GAPDH, and LDHA exhibited increased mRNA expression levels in preeclamptic placentas. Therefore, MMRDEGs may play a critical role in the mechanism of oxidative stress and inflammatory response in PE by mediating metabolic regulation and immune modulation, potentially serving as diagnostic biomarkers associated with mitochondrial metabolism in preeclampsia.